2011
DOI: 10.1159/000329361
|View full text |Cite
|
Sign up to set email alerts
|

Is a Patient Controller for Parkinson’s Disease Patients with Subthalamic Nucleus Deep Brain Stimulation Reasonable?

Abstract: Background: A patient controller (PC) is an optional device for patients with deep brain stimulation (DBS) to have limited control of their stimulator system. Objectives: We investigated the impact of a PC on DBS safety, most notably the handling/prevention of unexpected DBS failure in patients with Parkinson’s disease (PD). Methods: PD patients with subthalamic DBS were educated in the use of a PC. After a first impulse generator (IPG) replacement, data on the use of the PC were obtained from the patients’ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
3
0
6
Order By: Relevance
“…Our findings were consistent with those of other authors who have already reported an inverse correlation of TEED and IPG longevity . Longevity of the Kinetra, however, was shorter in previous studies when compared to our findings. This could be due to higher stimulation settings in these studies which we could not adequately verify through the published data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with those of other authors who have already reported an inverse correlation of TEED and IPG longevity . Longevity of the Kinetra, however, was shorter in previous studies when compared to our findings. This could be due to higher stimulation settings in these studies which we could not adequately verify through the published data.…”
Section: Discussionsupporting
confidence: 93%
“…Mean longevities were 40.2–83 months in Itrel ® II (Model 7425) , 37.8 months in Itrel III (Model 7425) , 25.1–44.9 months in Soletra ® (Model 7426) , and 19.7–52.4 months in Kinetra (Model 7428) , manufactured by Medtronic (Medtronic, Inc., Minneapolis, MN, USA), respectively. However, comparison of the available data might be difficult due to the inconsistently chosen replacement indications, such as replacement before complete IPG discharge , end of life (EOL) or complete depletion , or lacking telemetry . Moreover, data on the longevity of Medtronic's latest IPG for DBS, the Activa PC (Modell 37601), is so far missing.…”
Section: Introductionmentioning
confidence: 99%
“…In line with that, Allert et al. reported, in 27 consecutive PD patients treated with bilateral STN DBS, a mean of 28.6 days of hospital or rehabilitation stay for programming of the IPG.…”
Section: Discussionsupporting
confidence: 64%
“…The parameter settings are highly individual and may be changed at any programming session to optimize the patient's symptom relief. Most centers provide the patient with a handheld therapy controller for home use . The controller allows the patient to switch the device on and off, as well as to increase or decrease the electric stimulation within a window of electric parameters decided by the clinician at the programming session.…”
Section: Introductionmentioning
confidence: 99%
“…Der Magnetschalter dieser Impulsgeber kann auch von elektromagnetischen Feldern in der Umwelt aktiviert werden und so zu einem unbeabsichtigten Abschalten der THS führen. Der 2-Kanal-Impulsgeber Kinetra ® besitzt ebenfalls einen Magnet-empfindlichen Schalter (reed switch), der jedoch telemetrisch inaktiviert werden kann, sodass der Impulsgeber weitgehend unbeeinflusst von Magnetfeldern in der Umwelt ist [10]. Darüber hinaus gestattet der Kinetra ® eine grobe Kontrolle der Batteriekapazität, sodass es seltener zu einem unvorhergesehenen Batterieausfall kommt.…”
Section: Besonderheiten Der Verschiedenen Impulsgeber-modelleunclassified